2017
DOI: 10.1371/journal.pone.0175893
|View full text |Cite
|
Sign up to set email alerts
|

Voice disorder in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic disease characterized by progressive tissue damage. In recent decades, novel treatments have greatly extended the life span of SLE patients. This creates a high demand for identifying the overarching symptoms associated with SLE and developing therapies that improve their life quality under chronic care. We hypothesized that SLE patients would present dysphonic symptoms. Given that voice disorders can reduce life quality, identifying a potential SLE-related dysph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Voice disorders can lead to heightened susceptibility to depression and anxiety disorders, increased levels of stress, and diminished self-reported indicators of health. Effective communication heavily relies on spoken language, making dysphonia a significant challenge that can profoundly impact interpersonal interactions and diminish the overall quality of life [ 4 ]. Dysphonia, a condition affecting vocalization, manifests in various acoustic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Voice disorders can lead to heightened susceptibility to depression and anxiety disorders, increased levels of stress, and diminished self-reported indicators of health. Effective communication heavily relies on spoken language, making dysphonia a significant challenge that can profoundly impact interpersonal interactions and diminish the overall quality of life [ 4 ]. Dysphonia, a condition affecting vocalization, manifests in various acoustic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Many different kinds of illnesses are often revealed during speech production via the body's complex neuro-muscular system. For decades, speech studies [1][2][3][4] have shown that poorer voice quality, intelligibility, and/or agility during speech production are key indicators of motor impairment, often the result of neurodegenerative, autoimmune, and psychogenic illnesses. To help assess the capabilities of speakers' motor-speech coordination, carefully crafted elicitation protocols have been designed.…”
Section: Introductionmentioning
confidence: 99%
“…These include but are not restricted to Sicca syndrome [ 10 ], dry mouth syndrome [ 11 ] and body dehydration [ 12 ], hormonal alterations linked to pubertal [ 13 ], menopausal [ 14 ] and andropausal [ 15 ] status and acromegaly [ 16 ], cardio-vocal syndrome [ 17 ], respiratory disorders (e.g. chronic obstructive pulmonary disease [ 18 ] and asthma [ 19 ]), gastrointestinal reflux [ 20 ], autoimmune diseases such as rheumatic arthritis [ 21 ] and Sjögren’s syndrome [ 22 ], systemic lupus erythematosus [ 23 ], amyloidosis [ 24 ], cystic fibrosis [ 25 ], endocrinologic disorders such thyroid dysfunction [ 26 , 27 ] and anorexia nervosa [ 28 30 ], underweight versus overweight and obesity [ 31 , 32 ], and diabetes [ 33 ]. Table 2 highlights corresponding laryngeal symptoms.…”
Section: Introductionmentioning
confidence: 99%